O referencial teórico de Paulo Freire no ensino de ciências e na educação CTS: um estudo bibliométrico e epistemológico - Lopes, Gabriela Zauith Leite (2013)
The Science Teaching, spurred by the development of science and technology as well as the field of education, seeks paradigms that go beyond positivist approaches and linear knowledge production. Perceptions of the social dimensions of science and technology have led to this PhD study to realize a proposal within the dialogic Science Teaching and STS Education (Science, Technology and Society). Perceptions of the social dimensions of science and technology have led to this PhD study to realize a proposal within the dialogic Science Teaching and STS Education. The aim of this study is to verify the ownership of the theoretical framework of Paulo Freire in Science Teaching and Education CTS, represented by the scientific production of theses and dissertations and courses offered by the graduate. Represented by the research questions: How do I set the presence of referential Freire in STS Education and Teaching STS represented by the scientific production of theses and dissertations and the disciplines offered in graduate? What are the epistemological bases underpinning the theses in the field of Education and Higher Education STS adopted the theoretical Freire? The methodological procedures used include bibliometric research and epistemological analysis, with the construction of four matrices analysis, which reach the theoretical, epistemological, ontological and gnosiological of the studies analyzed. In bibliometric survey data collection was made on Bank CAPES thesis and Notebook Indicators Capes. To search for theses and dissertations search terms used were combinations of "STS Education" "Teaching STS" and "Science Education Paulo Freire. The data were processed in VantagePoint software and Excel ®. We analyzed 43 studies that used the theoretical perspective of Paulo Freire, 34 masters and nine doctoral. In Notebooks Indicators Capes data were collected from 57 subjects of 22 educational institutions in search of references related to Paulo Freire. Bibliometric analysis results indicate that the theses and dissertations are concentrated in the area of Education and Science and Mathematics at the Federal University of Santa Catarina, Universidade de Brasília and São Paulo University. To relate data from the Bank of Theses and Notebooks Indicators analyzed data from UFSC, UNB and USP with the literature of the subjects of their graduate programs, identifying literature Paulo Freire used: Pedagogy of the Oppressed and Pedagogy Autonomy. The epistemological analysis was performed by analysis of three matrices: 1) matrix ownership Freire's theoretical framework, 2) matrix paradigmatic STS , and 3) analysis matrix epistemological framework Freire. Results of the research show that the epistemological bases underpinning the theses in the field of STS Education and Science Education adopted the theoretical Freire point to changes that include critical-dialectical approaches. Work on Science Education seeks to revise the linear and positivist paradigm to which they are subjected. And work in STS Education /Science Teaching clarifies their limitations and seeks complementarity with the pedagogical thinking of Paulo Freire. Built in a humanistic and critical, the subject of knowledge is central, built and socio-historically mediated world. This study aims to add knowledge to the studies Freirean of Science Teaching and STS Education, in the sense that their results contribute to the expansion of critical mass on the need for theoretical research in Science Teaching in STS perspective.